Inherently separated syngas production from plastic waste fast pyrolysis integrated with volatile chemical looping conversion with CO₂ splitting - Liu, Guicai (2023)
To convert plastic waste into high-value products coupled with CO2 utilization, this study proposed a new concept to produce inherently separated syngas through fast pyrolysis integrated with volatile chemical looping CO2 splitting. Three conversion modes, i.e., redox, cracking and redox-cracking mixed modes, were evaluated using different catalyst, and found that cracking mode with Ni/Al2O3 or Ni/MgAl2O4 exhibited better fuel conversion and syngas separation performance than redox and mixed modes (using Ca2Fe2O5 and Ni/Ca2Fe2O5, respectively), achieving nearly full CO-H2 separation from the syngas product. Focusing on the cracking mode, higher temperature facilitated the fuel and coke conversion, due to the endothermic nature of both reaction stages. The syngas separation efficiency increased during 5 cycles and stabilized ∼95% while using Ni/MgAl2O4 catalyst. The redox between Ni0 and Ni2+ was inevitable for both cracking catalysts during multiple cycles due to the Ni-support interaction, limiting the full separation of syngas. The accumulation of low-reactive coke during multiple cycles was another important consideration. Ni/MgAl2O4 possessed weaker Ni-support interaction and less coke accumulation than Ni/Al2O3, thus performed better syngas separation efficiency. Therefore, it is crucial to minimize Ni-support interaction and the generation of high-graphitic coke for optimization.